3D ENDOSCOPIC MITRAL VALVE REPLACEMENT WITH BIOPROSTHESIS IN ELDERLY PATIENTS AT CARDIOVASCULAR CENTER, E HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To summarize the initial experiences and evaluate the early results of applying 3D endoscopic surgery for biological mitral valve replacement in the elderly.Subjects and methods: The study was conducted by cross-sectional method, retrospective data including all patients ≥ 60 years old, who underwent 3D endoscopic surgery for biological mitral valve replacement at the Cardiovascular Center of Hospital E between January 2021 and December 2023.Results: The study included 67 patients, with an average age of 65.6 ± 4.8 years, male/female ratio is 2/1. Before surgery: 74.6% NYHA 3-4 heart failure; 49.3% arrhythmia; 10.5% EF below 50%. Extracorporeal circulation time 155.3 ± 30.7 minutes; aortic clamping time 114.8 ± 26.6 minutes. 29.9% of patients underwent left atrial appendage suturing; 1.5% tricuspid valve repair. After surgery, prolonged mechanical ventilation time (over 2 days) 20.9%; intensive care unit stay 2.9 ± 1.7 days; hospital stay 13.3 ± 5.1 days. Complications included: ventricular rupture (3.0%), in-hospital death (3.0%), reoperation due to bleeding (4.5%), renal failure (3.0%), and cerebral infarction (1.5%).Conclusions: 3D endoscopic surgery for bioprosthetic mitral valve replacement has been routinely performed at E Hospital with positive results and needs further research on a larger number of patients over a longer period of time.
Keywords: Mitral valve, mitral bioprothesis, minimally invasive cardiac surgery, 3D endoscopic surgery.